Public Transit Subsidy: from the Economics of Welfare to the Theory of Incentives - Daniele Fabbri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
Public Transit is publicly managed almost all over Europe. Public intervention in this sector is due to market failures: economies of scale and misperceptions of social and private costs may cause an insufficient supply of transit services. These arguments have been thouroughly analyzed within the standard welfarist approach to the theory and practice of subsidization. Ramsey rules and cost-benefit analysis emerged as useful devices for the definition of subsidy allocation. However remedies to market failures should be traded-off against government failures. Lack of incentives, X-inefficiency, regulatory capture, bureaucracy power are common facts in the internal organization of public administration. If a public sector utility, for some reasons, can not be completely privatized, it may be "almost" privatized by means of quasi-market mechanisms. Auctioning, yardistick competition, incentive schemes, auditing, regulation through competition are the keywords for the renewed public involvment in public transit. All these mechanisms can be properly studied within the theoretical format of the incentives theory. This approach helps us to understand past experiences of transit firms incentives scheme and to appreciate the relevance of the empirical analysis of performance indicators. An important question that emerges is the definition of operational incentive contracts. In this paper we will discuss this problem by referring to past and recent experiments with performance based subsidization programs.
Keywords: 330